2014
DOI: 10.1371/journal.pone.0087732
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of Acoustic Signals in a Widely Distributed Frog: Relevance of Inter-Male Interactions

Abstract: Divergence of acoustic signals in a geographic scale results from diverse evolutionary forces acting in parallel and affecting directly inter-male vocal interactions among disjunct populations. Pleurodema thaul is a frog having an extensive latitudinal distribution in Chile along which males' advertisement calls exhibit an important variation. Using the playback paradigm we studied the evoked vocal responses of males of three populations of P. thaul in Chile, from northern, central and southern distribution. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
2
16
1
1
Order By: Relevance
“…) based on average values of calls obtained in the previous season from individuals not included in this study (e.g., Velásquez et al. ). Call recordings were made at 35°C, the preferred body temperature of L. chiliensis (Labra et al.…”
Section: Playback Experimentsmentioning
confidence: 99%
“…) based on average values of calls obtained in the previous season from individuals not included in this study (e.g., Velásquez et al. ). Call recordings were made at 35°C, the preferred body temperature of L. chiliensis (Labra et al.…”
Section: Playback Experimentsmentioning
confidence: 99%
“…También se ha descrito variación en los parámetros espectrales y temporales del canto de apareamiento entre poblaciones de P. thaul (Velásquez et al 2013), la cual se correlaciona con la divergencia genética entre ellas. Esta variación geográfi ca en el canto está acompañada por una variación en las respuestas vocales evocadas de machos de esta especie a cantos sintéticos de la misma u otra población (Velásquez et al 2014).…”
Section: Ecologíaunclassified
“…A recent study of geographic variation of the advertisement calls of this species has revealed the existence of three bioacoustic groups, differing in the structure of both temporal and spectral components, corresponding to northern, central and southern populations (Velásquez et al, 2013) (Velásquez, 2014). In addition, a study of evoked vocal responses (i.e., vocal responses that are elicited by a stimulus and do not correspond to spontaneous vocal activity) revealed that males of this species exhibit different vocal activity when confronted with local or foreign stimuli, implying intra-sexual selection in the origin of advertisement call divergence (Velásquez et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Males produce advertisement calls that attract females and promote the establishment of territories (Gerhardt and Huber, 2002). Geographic variation of these signals has been reported to occur in various cases (e.g., Nevo and Capranica, 1985;Pröhl et al, 2006Pröhl et al, , 2007Wilczynski and Ryan, 1999;Velásquez et al, 2013) and has been attributed to different factors such as environmental conditions affecting signal propagation (Wilczynski and Ryan, 1999), genetic or geographic distances (Bernal et al, 2005;Pröhl et al, 2006Pröhl et al, , 2007Velásquez et al, 2013), and/or sexual selection processes (Boul et al, 2007;Velásquez et al, 2014). However, few studies on the geographic variation of female preferences in response to male calls from populations of different geographical origin have been carried out.…”
Section: Introductionmentioning
confidence: 99%